Efektivitas Deep Back Massage dan Massage Endorphin terhadap Intensitas Nyeri Kala I Fase Aktif di BPM Setia : Effectiveness Deep Back Massage and Massage Endorphin Against Intensity of Pain in Active Phase I in BPM Setia - Artika Dewie; Mercy Joice Kaparang (Poltekita : Jurnal Ilmu Kesehatan, 2020)
The preferred delivery for every pregnant woman is labor with minimal pain. Labor Pain is caused by the process of contraction of the uterus in an effort to remove the fruit of pregnancy. One technique without drugs or non-pharmacological that can be to provide comfort to the mother in the face of labor is massage. The purpose of this study was to determine the effectiveness of the Deep Back Massage and Endorphin Massage methods on the intensity of pain in the active phase I at BPM Setia. This research was conducted from July to August 2019 at BPM Setia. The population in this study were all women who gave birth normally with a gestational age of 37 to 40 weeks when I active phase in Setia BPM during the study period. The sample size is 30 respondents. The results obtained showed that the deep back massage and endorphin massage each showed a p-value <0.005 which means that there were differences in the mean labor pain of the first stage of the active phase which was significant before and after the endorphin massage action. Likewise for the Deep Back Massage. Further analysis of endorphin massage and deep back massage, turned out to produce a p-value of 0.74 (> α 0.05), which means that there is no difference in the effectiveness of the deep back massage and endorphin massage on labor pain in the active phase I at BPM Setia.